CD47 expression is decreased in hematopoietic progenitor cells in patients with myelofibrosis - Nonino, Alexandre (2019)
Myelofibrosis (MF) is characterized by increased circulating hematopoietic progenitor cells (HPCs), abnormal cytokine levels, and the survival advantage of neoplastic progenitors over their normal counterparts, which leads to progressive disappearance of polyclonal hematopoiesis. CD47 is a surface glycoprotein with many functions, such as acting as a phagocytosis inhibitor of the expressing cell, that is increased in normal hematopoietic stem and progenitor cells mobilized into the blood and several human cancer-initiating cells, such as in acute myeloid leukemia. We compared CD47 expression in hematopoietic stem and progenitor cells of patients with MF and controls and found it to be decreased in progenitors of MF. Exposure of control HPCs to the cytokines transforming growth factor β and stromal-derived factor 1, which are important regulators of hematopoietic stem cell cycling and are overexpressed in patients with MF, did not modulate CD47 expression.